Deducing the cellular mechanisms associated with the potential genotoxic impact of gold and silver engineered nanoparticles upon different lung epithelial cell lines in vitro. Issue 1 (2nd January 2022) - Llewellyn, Samantha V.; Parak, Wolfgang J.; Hühn, Jonas; Burgum, Michael J.; Evans, Stephen J.; Chapman, Katherine E.; Jenkins, Gareth J. S.; Doak, Shareen H.; Clift, Martin J. D.
Abstract: Human ENP exposure is inevitable and the novel, size-dependent physicochemical properties that enable ENPs to be beneficial in innovative technologies are concomitantly causing heightened public concerns as to their potential adverse effects upon human health. This study aims to deduce the mechanisms associated with potential ENP mediated (geno)toxicity and impact upon telomere integrity, if any, of varying concentrations of both ∼16 nm (4.34 × 10 −3 to 17.36 × 10 −3  mg/mL) Gold (Au) and ∼14 nm (0.85 × 10 −5 to 3.32 × 10 −5  mg/mL) Silver (Ag) ENPs upon two commonly used lung epithelial cell lines, 16HBE14o − and A549. Following cytotoxicity analysis (via Trypan Blue and Lactate Dehydrogenase assay), two sub-lethal concentrations were selected for genotoxicity analysis using the cytokinesis-blocked micronucleus assay. Whilst both ENP types induced significant oxidative stress, Ag ENPs (1.66 × 10 −5  mg/mL) did not display a significant genotoxic response in either epithelial cell lines, but Au ENPs (8.68 × 10 −3  mg/mL) showed a highly significant 2.63-fold and 2.4-fold increase in micronucleus frequency in A549 and 16HBE14o − cells respectively. It is hypothesized that the DNA damage induced by acute 24-h Au ENP exposure resulted in a cell cycle stall indicated by the increased mononuclear cell fraction (>6.0-fold) and cytostasis level. Albeit insignificant, a small reduction in telomere length was observed following acute exposure to both ENPs which could indicate the potential for ENP mediated telomere attrition. Finally, from the data shown, both in vitro lung cell cultures (16HBE14o − and A549) are equally as suitable and reliable for the in vitro ENP hazard identification approach adopted in this study.